2021
DOI: 10.26508/lsa.202000908
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell entry to lymphatic capillaries is orchestrated by CD44 and the hyaluronan glycocalyx

Abstract: DCs play a vital role in immunity by conveying antigens from peripheral tissues to draining lymph nodes, through afferent lymphatic vessels. Critical to the process is initial docking to the lymphatic endothelial receptor LYVE-1 via its ligand hyaluronan on the DC surface. How this relatively weak binding polymer is configured for specific adhesion to LYVE-1, however, is unknown. Here, we show that hyaluronan is anchored and spatially organized into a 400–500 nm dense glycocalyx by the leukocyte receptor CD44.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 93 publications
1
25
0
Order By: Relevance
“…Although the capacity of certain immune cell populations for HA synthesis had been reported previously by other workers [108][109][110][111][112][113], the key significance of the glycosaminoglycan for lymphatic entry and migration was completely overlooked. Generated primarily by the hyaluronan synthase II isoenzyme that makes polymer chains of up to 10,000 saccharide units in length (equivalent to contour lengths of several microns), the HA glycocalyx of human and murine monocyte-derived dendritic cells and their endogenous counterparts in tissue constitutes a dense corona of some 500 nm thickness, as estimated by conventional and high-resolution Airyscan confocal imaging using either biotinylated HA-binding protein (bHABP) or biotinylated versican G1 domain (bVG1) and fluorescent streptavidin as probes (Figure 3) [114]. The constituent HA polymers of the glycocalyx are, in turn, anchored to the plasma membrane via CD44, as deduced from analyses of DCs isolated from receptor knockout mice, which indicated the cd44 −/− cells continue to synthesise HA but fail to retain a glycocalyx on their surface.…”
Section: Lymphatic Entry: the Immune Cell Ha Glycocalyx And Its Engagement With Lyve-1mentioning
confidence: 99%
“…Although the capacity of certain immune cell populations for HA synthesis had been reported previously by other workers [108][109][110][111][112][113], the key significance of the glycosaminoglycan for lymphatic entry and migration was completely overlooked. Generated primarily by the hyaluronan synthase II isoenzyme that makes polymer chains of up to 10,000 saccharide units in length (equivalent to contour lengths of several microns), the HA glycocalyx of human and murine monocyte-derived dendritic cells and their endogenous counterparts in tissue constitutes a dense corona of some 500 nm thickness, as estimated by conventional and high-resolution Airyscan confocal imaging using either biotinylated HA-binding protein (bHABP) or biotinylated versican G1 domain (bVG1) and fluorescent streptavidin as probes (Figure 3) [114]. The constituent HA polymers of the glycocalyx are, in turn, anchored to the plasma membrane via CD44, as deduced from analyses of DCs isolated from receptor knockout mice, which indicated the cd44 −/− cells continue to synthesise HA but fail to retain a glycocalyx on their surface.…”
Section: Lymphatic Entry: the Immune Cell Ha Glycocalyx And Its Engagement With Lyve-1mentioning
confidence: 99%
“…Besides the adhesion molecules ICAM-1 and VCAM-1, another well-described molecule that mediates DC trafficking to dLNs is the hyaluronan receptor LYVE-1, which is exclusively expressed in lymphatic capillaries [47]. A recent study showed that during inflammation the leukocyte receptor CD44 organizes the distribution of hyaluronan and regulates DC adhesion and transmigration through the lymphatic endothelium [125]. Further molecules reported to guide DC migration through afferent lymphatics are summarized in Table 1.…”
Section: Adhesion Moleculesmentioning
confidence: 99%
“…ICAM-1 accumulates on microvilli projections surrounding adherent DCs in a manner dependent upon the conformational change of β2 integrin on the DC, promoting DC crawling over the lymphatic endothelial basolateral surface and transendothelial migration [ 102 ]. Formation of such endothelial transmigratory cups is induced through ligation of the lymphatic endothelial receptor LYVE-1 engaging with its ligand hyaluronan (HA) [ 91 ], organized in a dense 400–500 nm thick glycocalyx on the DC surface by the leukocyte receptor CD44 [ 92 ]. Disruption of LYVE-1:HA interactions by gene deletion, antibody blockade or depletion of the HA glycocalyx impair DC adhesion, transmigration and lymphatic trafficking, resulting in diminished antigen-specific T-cell immune responses in draining lymph nodes [ 91 ].…”
Section: Acute Inflammation and Infectionmentioning
confidence: 99%
“…It is possible that CCL2:CCR2 may play a role at this stage too, as “cords” of DCs were visible inside lymphatic vessels of CCR2-deficient mice, suggestive of a defect in intraluminal crawling rather than due to impaired vessel entry [ 123 ]. Such lymphatic cords are also apparent when increased levels of endogenous HA are incorporated into the CD44-held glycocalyx on DCs, by antibody-induced potentiation of CD44:HA interactions [ 92 ]. Adhesion of these DCs to lymphatic endothelium was found to be greatly enhanced; however, transit to draining lymph nodes was impaired and such cells remained stuck in initial capillaries.…”
Section: Acute Inflammation and Infectionmentioning
confidence: 99%
See 1 more Smart Citation